PENGARUH LATIHAN AGILITY LADDER TERHADAP MOBILITY TENIS LAPANGAN ATLET USIA 12-14 TAHUN - Rahmawati, Divya Zuhra; Aprilianto, Dwi (AHSANTA JURNAL PENDIDIKAN, 2024)
This study aims to analyze the Effect of Agility Ladder Training on Tennis Mobility of Athletes Aged 12-14 Years. This study uses a quasi-experimental design with a One Group-Pretest Posttest research design. The population in this study was 15 athletes. The study was conducted at the Military Resort Command (Korem) tennis in Bandar Lampung City with a research period of December 15, 2023 to February 1, 2024. The results of the study based on the results of the effectiveness test on 15 research subjects, there was an average initial test result for Tennis Mobility, namely Mean = 8.2667 which shows the difference between the pre-test and post-test results, t-test results = 26.183, df = 14 and p-value = 0.00 <0.05 which indicates that there is a significant difference between before and after being given agility ladder treatment on tennis mobility of athletes aged 12-14 years. Based on the research results above, agility ladder training on tennis field mobility of athletes aged 12-14 years can be applied and agility ladder training is effective in improving tennis field mobility abilities.